Evolution of high-quality economic development: a bibliometric analysis - Huang, Yi; Yan-Ling, Tan; Mohamad Shafi, Roslina (Universiti Teknologi MARA Selangor, 2025)
China's current development focuses on high-quality economic development (HQED), which aims to enhance the efficiency and quality of growth while simultaneously advancing social, economic, and environmental progress. This approach not only improves the quality of life but also increases national wealth. Despite its significance, HQED has not garnered much global attention. To address this gap, this study employs bibliometric methods and VOS viewer software to analyse the evolution and primary research hotspots of HQED. The findings reveal that the evolution of HQED research can be divided into two distinct periods: (i) from 2018 to 2020, when HQED was still in its infancy, and (ii) from 2021 to 2023, which saw a rapid increase in the number of HQED publications. China has emerged as the leading contributor to HQED research. The journal "Sustainability" serves as the main outlet, while the Chinese Academy of Sciences is the most active institution in HQED studies. The most cited author is Zhang Wei. The research is organised into several key clusters: Cluster 1 focuses on research methods used in HQED studies, while Clusters 2 and 3 introduce more green elements and considerations of environmental quality. Cluster 4 emphasises the importance of innovation and financial development. Clusters 5 and 6 address topics related to the digital economy, digital finance, and digital transformation, whereas Cluster 7 highlights China's focus on high-quality development. broaden the scope of HQED to include areas such as green innovation, digital economies, and human capital.